PENGARUH LATIHAN INTERVAL (INTERVAL TRAINING) TERHADAP DAYA TAHAN VO2MAX PADA ATLET KARATE KUMITE JUNIOR PUTERA DOJO INKAI NAVY KIDS KOTA TANJUNGPINANG - Lukman, Lukman; Zainur, Zainur; Nita Wijayanti, Ni Putu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: The objective of this research is to analyze the endurance the male Junior Kumite athletes from INKAI Navy Kids Tanjungpinang. The goal of this research is to prepare them to be better in the match and maintain their endurance so that they may be able to fight their rival and accomplished the higher rank of achievement. This research is applying qualitative method with experimenting the samples; by the population of the sample is the male Junior Kumite athletes from INKAI Navy Kids Tanjungpinang. The data which applied in this research is the whole population of the sample; there are 6 athletes in total. The instrument which applied in this research is bleep test in order to convert the endurance. Then the data are analyzed by statistic, to examine the normal level by applying the liliefors to significant level α 0,05. The hypothesis from the writer in this research is the influence of the interval training toward the endurance of the athletes. Based on the analysis of T-experiment, the summary of the research is 6,15 T-convert and 2,015 T-table. The writer concludes that T-convert > T-table. Based on the analysis to the statistic data, the average (mean) of pre-test is 34,25 and post-test is 36,77. The writer concludes that the data are normally distributed. Therefore, this research shows the influence of the interval training toward the endurance of male Junior Kumite athletes from INKAI Navy Kids Tanjungpinang. Keywords: Training Interval ( Interval Training ) , Endurance VO2Max